THE IMPACT OF CORPORATE GOVERNANCE PRACTICES ON POST-MERGER PERFORMANCE - Ali İhsan Akgün (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The relation between the post-merger performance and corporate governance mechanism is examined using Linear regression model for a sample of US, Canada, EU-28 and Western European countries listed firms for the period from 2003 to 2012. We also examine as to whether the use of International Financial Reporting Standards (IFRS) improves corporate transparency, therefore, increasing financial reporting quality. Using a sample of banks from international countries, we present the following key findings: post-merger performance is significantly better common law in countries than code law in countries with better IFRS group banks during the post-merger performance. We also find that local GAAP reporting allows a more transparent assessment of financial performance on the basis of traditional indicators making it a superior tool for assessing potential acquisition targets. This study analysis changes in a country legal regulation as a measure of corporate governance and shows that these regulations play an important role in merger activity. Legal origins and owner-protection mechanisms are important in explaining the relationship between the quality of accounting standards and corporate governance practices following IFRS adoption. Overall, our empirical findings result consistent with Ciobanu (2015) find that merger and acquisition is influenced both the legal origin and accounting regulations.